STEMM simulation program inspires underprivileged middle school students - Daniel, Laura; N-Wilfong, Donamarie (American Journal of STEM Education, 2024)
“What do you want to be when you grow up?” While many students are asked this question at young ages, as students develop their interests and recognize their academic strengths during the middle school years, the timing is right to revisit this question. However, to answer this question, students need a solid understanding of what careers exist. Hence, to promote career exposure and exploration during the critical middle school years, a Science, Technology, Engineering, Mathematics, and Medicine (STEMM) on the Go (SOTG) program was created by a healthcare simulation center that brought STEMM simulations and activities into underprivileged 7th and 8th grade classrooms. Outcomes were measured with STEMM interest surveys and program evaluations. Results showed statistically significant increases in students’ interest in the fields of mathematics and medicine. Students reported feeling more confident in math and science skills after the program. Students and middle school administrators reported high levels of program satisfaction. The SOTG program is a promising experiential initiative that introduces future generations to STEMM careers and inspires them to further their education, while cultivating lifelong skills in a fun and inclusive environment. This article provides readers with guidelines to create and implement SOTG programs, thus broadening the field of simulation education and providing crucial STEMM exposure to underserved populations.